Enhancing High School Students Problem Solving Ability in Algebra through Artificial Intelligence Based Learning - Qurohman, M. Taufik (SAINTIS Publishing, 2024)
This research is an experimental study conducted with a population of PGRI 1 Taman Pemalang High School students. The sample consisted of 11th grade students from the odd semester of 2024/2025, selected using cluster random sampling to determine the experimental and control classes. This study aimed to improve students' problem solving skills in algebra in a school environment, focusing on Artificial Intelligence based learning and student independence. The algebra topics covered included linear equations, quadratic equations, polynomials, and systems of linear equations. This research involved two main variables: Artificial Intelligence (AI) and problem-solving ability in algebra. Data was collected using questionnaires, tests, and documentation methods. Data analysis was conducted using a two way ANOVA with factorial interaction in a 2x2 design, supplemented by the Bonferroni test as a post hoc analysis. The results showed that students exposed to Artificial Intelligence-based learning demonstrated significantly higher problem solving ability in algebra compared to students taught with conventional methods. Additionally, students with high independence exhibited better problem-solving ability compared to those with low independence. These findings suggest an interaction effect between Artificial Intelligence based learning and student independence on problem solving ability in algebra. Specifically, students with high independence who underwent Artificial Intelligence based learning achieved the highest problem solving ability compared to all other interaction types. This emphasizes the positive synergistic effect of Artificial Intelligence based learning and student independence in enhancing problem solving ability in algebra.